The short-term labor market impact of Venezuelan immigration in Peru - Celia P. Vera; Bruno Jiménez (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2022)
Peru is the second-largest recipient of Venezuelans worldwide. We combine newly available data on Venezuelans living in Peru and the Peruvian Household Survey to assess the impact of Venezuelan migration on natives' wages and employment. The initial regression analysis exploits the variation in supply shifts across education-experience groups over time. It indicates that immigration in Peru had no adverse impact on native wages. However, the paper highlights that in Peru immigrants and natives with similar education and experience are likely to work in different occupations. The subsequent analysis based on occupational clustering confirms the null effect on wages and indicates that a 20% increase in immigrants decreases formal employment by 6%. We do not find evidence for changes in employment composition toward informality so that migration operates through the extensive margin of employment. We report evidence in favor of immigrants being a close substitute to the least productive natives, suggesting that firms substitute native formal labor for low-cost immigrant informal labor.
Keywords: J24; J31; J46; 330; Immigration; education-experience cells; occupation cells; informality